Padrões de características de cuidado parental e marcadores da qualidade da alimentação em escolares brasileiros - Ana Maria Miranda de Araujo (2017)
Introduction: The eating behavior in the Brazilian teens populations is characterized by high intake of ultra-processed foods and a low intake of fruits and vegetables. Thus fact is of great relevance to the public health systems by being a risk factor for the occurrence of chronic non-communicable diseases (NCDs), and 20% of Brazilian teenagers are overweight and about 10% have hypertension. In this context, the development of public policies should take into account factors that influence eating behavior, such as parental care, considered a important determinant of food intake for children and adolescents. Objective: To recognize patterns involving features of parental care and to review the association between these patterns and indicators of quality of food intake in elementary schools in Brazil. Methods: The data from the Brazil National Survey of School Health (PeNSE) were used; this survey was conducted in 2012 with a final sample of 109,104 ninth-grade students of the elementary school. To identify patterns of parental-care features, a principal component analysis was performed with 10 parental-care features toward adolescents. As for school nutrition were used issues involving the consumption of 4 food/ food groups eating healthy markers, 6 food/food group markers not healthy and a score feed. Linear regressions were used to describe sociodemographic patterns. Logistic regression was used to analyze the association between the studied patterns and indicators of food-intake quality. Results: Three patterns of parental care wereidentified. Pattern 1 (Watch) is represented by the parents' knowledge of their children's routine, while pattern 2 (Drugs) is represented by the parent's concern about the use of alcohol and tobacco by their children and, finally, pattern 3 (Meals) is represented by eating meals together as a family and having breakfast on most days. The pattern Watch and Meals was those with the largest membership in the healthy food consumption (positive association to markers of healthy food and negative to unhealthy food). The former pattern, however, stands out for being the only one with positive association with all the factors under analysis independently. Meanwhile the Drugs pattern (pattern 2) had favorable association with fewer factors for healthy food and also showed positive association with some food unhealthy nutrition markers. Conclusion: The recognition of patterns related to parental-care features and the study of their association with the food-intake quality of Brazilian teenagers showed the importance of active participation of parents in the daily life of school children toward the development of healthy eating habits.